EVALUASI PENERAPAN PPH PASAL 22 ATAS PEMBELIAN BARANG YANG DIBIAYAI DENGAN APBN DI PENGADILAN TATA USAHA NEGARA MANADO - Mapanawang, Maria Angelitha; Sondakh, Jullie; Pusung, Rudy (Universitas Sam Ratulangi, 2018)
Each country has several sources of tax revenue, non-tax revenues and grants. From these sources of income, the tax becomes one. This research is intended to find out and apply whether Article 22 Income Tax on the purchase of goods financed by APBN in Manado State Administrative Court has been implemented in accordance with the established rules, namely Regulation of the Minister of Finance of the Republic of Indonesia Number 107/PMK.010/2015 and PMK 242/PMK.03/2014. Period of data taken is 2016. Type of research used is descriptive which will discuss about the implemeniation of Article 22 Income Tax on the purchase of goods financed by the State Budget at the State Administrative Court of Manado. The type of data used is qualitative data proof SSP PPh Article 22. The results of this study indicate Calculation, Payment, and Reporting on the procurement of goods financed by the state budget at the State Administrative Court of Manado not in accordance with the rules it stipulates from the application of Manado State Administrative Court Record has been in accordance with existing regulations.Keywords : calculation, registration, payment, reporting, article 22 income tax